Хронологія поселень черняхівської культури в лісостепу між Дніпром та Сіверським Дінцем - Любичев, М.В. (Археологія, 2011)
Знахідки з шарів і «умовно закритих» комплексів із поселень черняхівської культури дніпро-донецького лісостепу поділено на хроноіндикатори першого рівня та другого, що дозволило визначити час побутування пам’яток. Относительная и абсолютная хронология строится на основе закрытых комплексов погребений. Наличие их в черняховской культуре, оформленных в хронологические системы, позволяет «контролировать» хроноиндикаторы из
поселений. Датирующие находки на черняховских поселениях в лесостепной зоне между Днепром и Северским
Донцом (проанализировано 35 поселений) систематизированы в хроноиндикаторы первого уровня с твердой и до-20 ISSN 0235-3490. Археологія, 2011, № 4
вольно узкой датировкой изделий (фибулы, стеклянные сосуды, пряжки и костяные гребни) и второго — с широкой датировкой (фрагменты амфор). Хроноиндикаторы первого уровня присутствуют в комплексах фаз 3—5 хронологии черняховских могильников украинской лесостепи в системе Е.Л. Гороховского, более всего — в фазе 4
(350—400 гг.). На могильнике, прилегающем к поселению Войтенки с большим количеством хроноиндикаторов,
выделено две фазы (фазы 4 и 5, по Е.Л. Гороховскому, или ступени С3/D1 и D1, по Тейралу, периоды 4 и 5 в системе
О.А. Гей—И.А. Бажана). Характерные для них хроноиндикаторы первого уровня встречены и на поселении.
Черняховские поселения в регионе появились не ранее фазы 3 (330—380 гг.), однако большинство их, вероятнее всего, относится к фазам 4 и 5 (370/380—410/420 гг.). The relative and absolute chronology is based on closed complexes of burials. Issued into chronological systems, they allow
«controlling» the chronological indicators from the settlements. Dating finds from Chernyakhiv culture settlemenrs in the
forest-steppe area between the Dnipro and the Siverskyi Donets Rivers (35 settlements analyzed) are systematized into the
first level chronological indicators with definite and quite narrow dating of the items (fibulae, glass vessels, buckles, and bone
combs) and the second level ones (amphorae fragments). There are first level chronological indicators at complexes of the
phases 3—5 in Ye.L. Horokhovskyj’s chronological system of Chernyakhiv culture burial grounds in Ukrainian forest-steppe
zone, while most of them are in the phase 4 (350—400). There are two phases of development at the burial ground adjacent to
Voitenky settlement with a considerable number of chronological indicators (phases 4 and 5, by Horokhovskyj, or steps С3/D1
and D1 by Tejrala, or periods 4 and 5 in O.A. Hei and I.A.Bazhan’s system). Chronological indicators peculiar for them are also
found at the settlement.
Chernyakhiv culture settlements in the region appeared not earlier than the phase 3 (330—380), however, their majority
most probably refer to the phases 4 and 5 (370/380—410/420).